Comparing phonon dephasing lifetimes in diamond using Transient Coherent Ultrafast Phonon Spectroscopy - Lee, K; Sussman, B; Nunn, J; Lorenz, V; Reim, K; Jaksch, D; Walmsley, I; Spizzirri, P; Prawer, S (2010)
Transient Coherent Ultrafast Phonon Spectroscopy (TCUPS) is utilized to study phonon dephasing lifetimes in various diamond types. Samples of natural, chemical vapour deposited, and high pressure high temperature diamond are compared showing significant differences. Dephasing mechanisms are discussed. © 2010 Elsevier B.V. All rights reserved.